Collective equity participation in companies by industry and company size (2018)
This research analyzes the equity collective participation in the Colombian economy, according to the size of the companies and industry. To accomplish this objective, three economic industries were selected purposeful by maximum variation according to activity and equity volume, where companies were classified by size, analyzing their equity account compositions. The results are interpreted according to the theories of the agency or stock value, the dividend policy and the equity property rights, concluding that a greater participation exists as the size of the companies grows but not that of the sector. © 2018, Universidad del Zulia. All rights reserved.